Little maud - Zhou, Denis WanXian (2015)
Little Maud is a FYP short film that I produced and is inspired by the poem, Little Sleep’s-Head Sprouting Hair in the Moonlight written by the American poet Galway Kinnell. It takes the essentials of the poem, which is about a father’s fears of his young daughter growing distant from him in future, and writes a film about the psychological journey a particular father goes through in his mind for his daughter, Little Maud. As a result, a fantasy drama is made that deals with the universal themes of a father’s fears and paranoia in regards to the growing up of his daughter.